Evaluation of indoor air dose rate based on Cs‐137 depth distribution in surrounding artificially paved surfaces surveyed 10 years after the Fukushima Daiichi nuclear power plant accident - Hikaru Kobayashi; Masahito Suto; Kentaro Otsuki; Kazuya Yoshimura; Hiroko Yoshida (Japan Architectural Review, 2023)
Abstract Understanding residual radioactive contamination state and the resulting radiation environment is vital before reconstructing the lives of residents in areas affected by nuclear power plant accidents. In this study, we surveyed the depth profiles of Cs‐137 in three artificially paved ground surfaces: impermeable asphalt, permeable asphalt, and concrete, in areas affected by the Fukushima Daiichi Nuclear Power Plant accident after a period of 10 years and analyzed the gamma‐ray air dose rate distribution in a two‐story wooden house model surrounded by different ground surfaces using the Particle and Heavy Ion Transport code System of the Japan Atomic Energy Agency. The air dose rate distribution tendencies within the building for different surrounding ground surfaces were clarified by analyzing the transport of gamma rays emitted from the Cs‐137 in the ground. Moreover, the shielding effect of an ordinal concrete fence on the indoor air dose rate was analyzed. The analysis showed that the indoor air dose rate was higher in an environment with artificial pavement than in that with a soil surface, and even a simple measure, such as installing an ordinal concrete fence, could significantly reduce indoor radiation dose rates.